Exploring the Effect of Gold Support on the Oxygen Reduction Reaction Activity of Metal Porphycenes. Issue 23 (13th November 2018) - Anand, Megha; Siahrostami, Samira; Nørskov, Jens K.
Abstract: It has been a long‐standing goal to find alternative, cost effective catalysts for oxygen reduction reaction (ORR) in fuel cells. Molecular complexes capable of efficiently catalyzing ORR, when supported on a conducting solid surface could provide interesting hybrid materials combining the best of homogeneous and heterogeneous catalysis. We use density functional theory to study the ORR activity of molecular (unsupported) and gold supported 3d metal (II)‐porphycenes (MPc). All the 3d metal‐porphycenes adsorb strongly on the Au(111) support with negative free energy of formation ranging from 1.0–3.0 eV while solvation lowers the energy of molecular MPc by only 0.5 eV compared to the gas phase. These indicate that the 3d MPc are stable and anchored firmly to the gold surface under ORR conditions. Based on our analysis, the gold support enhances the ORR activity in some of the examined MPc systems. We find that the molecular MnPc and FePc are the best ORR electrocatalysts with theoretical overpotentials of 0.44 V and 0.36 V. This work highlights the important role of the support in preserving/increasing the activity of molecular catalyst. Abstract : The role of conducting solid support in enhancing/preserving the ORR activity of molecular catalysts is investigated with DFT. Such combination makes use of the best of homogeneous and heterogeneous catalysis.